2010
DOI: 10.1007/82_2010_31
|View full text |Cite
|
Sign up to set email alerts
|

VZV T Cell-Mediated Immunity

Abstract: Primary varicella-zoster virus (VZV) infection (varicella) induces VZV-specific antibody and VZV-specific T cell-mediated immunity. T cell-mediated immunity, which is detected within 1-2 weeks after appearance of rash, and consists of both CD4 and CD8 effector and memory T cells, is essential for recovery from varicella. Administration of a varicella vaccine also generates VZV-specific humoral and cellular immune responses. The memory cell responses that develop during varicella or after vaccination contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(154 citation statements)
references
References 75 publications
4
138
2
Order By: Relevance
“…In some studies, CD8 ϩ T cells were either undetected or present at low frequencies following VZV infection or vaccination in healthy subjects, in contrast to the more abundantly and frequently detected VZV-specific CD4 ϩ T cells (1). A VZV glycoprotein E vaccine induced VZV-specific CD4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, CD8 ϩ T cells were either undetected or present at low frequencies following VZV infection or vaccination in healthy subjects, in contrast to the more abundantly and frequently detected VZV-specific CD4 ϩ T cells (1). A VZV glycoprotein E vaccine induced VZV-specific CD4…”
Section: Discussionmentioning
confidence: 99%
“…T cell responses are necessary to control latent VZV in the sensory ganglia. A lack or a declining level of CMI to VZV has been associated with a higher risk of development of herpes zoster (1).…”
mentioning
confidence: 99%
“…Similar to CMV, analysis of the cellular responses to VZV and HSV has primarily focused upon lytic cycle antigens. These studies have also demonstrated diversity in the antigenic targets of HSV and VZV-specific T cells, with immunodominant responses generated in response to both structural antigens, including tegument proteins and surface glycoprotein and nonstructural antigens (68,69). Phenotypically, HSV and VZV-specific T cells in asymptomatically infected donors more closely resemble EBV-specific T cell populations, although their frequency is generally an order of magnitude lower (70)(71)(72).…”
Section: T Cell Immunity To Ebv and Other Human Herpesvirusesmentioning
confidence: 97%
“…23 Amongst those, glycoprotein E (gE), IE62, and IE63 were defined as being immunodominant. [24][25][26][27][28] The screening approaches that led to these findings mainly used memory T-cell populations which were expanded from PBMC of latently infected healthy individuals by antigen-specific stimulation over a culture period of several days to weeks. However, prolonged culturing may favor the proliferation of certain T-cell specificities over others and, consequently, the observed profile may not necessarily reflect the hierarchy of immunogenicity of different VZV antigens in vivo.…”
Section: Varicella-zoster Virus Glycoproteins B and E Are Major Targementioning
confidence: 99%